TINJAUAN YURIDIS KEDUDUKAN KEUANGAN DESA BERDASARKAN UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA - Tegar Firmandani; Emilda Firdaus; Abdul Ghafur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Rural Financial position based on Law Number 6 Year 2014 About Desa use of Article 18B paragraph (2) of the Constitution of the Republic of Indonesia Year 1945 as an legal fundament. But juridical Law Number 6 of 2014 on regulating the village especially problematic because the Financial village of Article 18B paragraph (2) does not regulate the village but set the unity of indigenous people. The arrangement of the traditional village of in accordance with the norms of Article 18B paragraph (2) of the Constitution of the Republic of Indonesia Year 1945. However, the setting of the village of New Order juridisnya questionable validity. The aim of this thesis, namely; First, to find out how the financial position of the village. Secondly, to find out how the ideal form of financial arrangements villages.This research is normative, which made the approach to find the law for a case in concerto. that approach find how to find the relevant facts, then find the law in abstracto the right to object under study. Data sources used include primary, secondary, and tertiary data. Data collection techniques using literature study.From the research, there are two main problems that can be inferred. First Position based Rural Finance Act Number 6 of 2014 Concerning the Village is basically very similar to the concept of State Finance. Second, Act Number 6 of 2014 concerning the village should be in Judicial Review by the Constitutional Court prior to this Law governing the Village of New Order is contrary to the Constitution of the Republic of Indonesia Year 1945, the legal fundament. Suggestions author, First, suggest to the Constitutional Court to annul Article About Financial village. Secondly, the Government and the House of Representatives is expected to create new legislation on the countryside.Key words: Village - Financial Village